"Writing on the wall social media, the first 2000 year - "Standage, Tom" (London, 2013)
Today we are endlessly connected: constantly tweeting, texting or e-mailing. This may seem unprecedented, yet it is not. Through out history, information has been spread through social networks, with far-reaching social and political effects. Writing on the Wall reveals how an elaborate network of letter exchanges forewarned of power shifts in Cicero's Rome, while the torrent of tracts circulating in sixteenth century Germany triggered the Reformation. Stand age traces the story of the rise, fall and rebirth of social media over the past 2,000 years offering an illuminating perspective on the history of media and revealing that social networks do not merely connect us today - they also link us to the past.
Keywords: "Social media, Mass media, Social networks"